Malassezia Furfur Pada Pitriasis Versikolor Dan Malassezia Folikulitis - HENDRA TARIGAN (CV. Jasa Sukses Abadi, 2022)
The skin is one of the largest organs of the body that hosts various communities including organisms that are harmless but can also be potential pathogens. Malassezia is part of the normal skin flora (microbiome). Malassezia also has a potential pathogen which under suitable conditions can invade the stratum corneum and manifest in various diseases including pityriasis versicolor and Malassezia folliculitis. Pityriasis versicolor (PV) is a chronic infectious disease of the skin caused by the fungus Malassezia furfur, is characterized by hypopigmented or depigmented patches with scaling. Malassezia folliculitis is an inflammatory condition caused by Malassezia involving the deeper unit, the pilo-sebaceous. Pityriaris versicolor and malassezia folliculitis are global skin diseases. Pityriasis versicolor and malassezia folliculitis often occur in tropical and hot climates and have high humidity and temperature, such as in Indonesia. In Indonesia, it is estimated that 50% of the population suffers from PV. This disease can affect all groups ranging from children to the elderly. With the high incidence of PV and malacezia folliculitis in Indonesia, the authors are interested in making this reference. The purpose of writing this report is to make the authors and readers better understand the characteristics of these two diseases, to be able to diagnose and treat them appropriately and to take preventive measures so as to reduce the incidence of PV and folliculitis malassezia in Indonesia.